Formalisasi sektor informal: Proses, faktor pengaruh, dan dampak pada pelaku usaha sektor informal di Kota Palembang - Armansyah Armansyah; Sukamdi Sukamdi (Jurnal Kependudukan Indonesia, 2021)
This study aims to examine the process of formalizing informal sector through an analysis of characteristics of informal and formal sectors, factors affecting the formalization process, and its impact on informal sector actors in Palembang City. This study combines quantitative and qualitative methods with sequential explanatory designs. Quantitative data collection are conducted through survey, while qualitative data are gathered through in-depth interviews. Informants for this study are informal business actor who stayed in Palembang and have run their business for at least 1 year. Quantitative data analysis using Chi-square test and descriptive frequencies, while qualitative data analysis uses three stages, namely, reduction, display, and conclusion. The formalization process can be classified into three stages, namely the informal, transition, and formal stages. Most informal business actors in Palembang are still at the informal stage. The process of formalizing the informal sector in Palembang does not occur systematically, but rather with random or up and down patterns. The results also shows that the process of formalization of the informal sector is largely based on the initiative of business actors. In addition, informal businesses that have undergone a formalization process tend to have better income and business security.